2006
DOI: 10.1021/la061596s
|View full text |Cite
|
Sign up to set email alerts
|

Microgels Loaded with Gold Nanorods:  Photothermally Triggered Volume Transitions under Physiological Conditions

Abstract: Photothermally driven volume transitions in polymer microgels have promising applications for site-specific drug delivery and photodynamic therapy. We studied the temperature-induced volume phase transitions for a series of thermoresponsive microgels of various compositions to find a system with a sharp transition in the physiologically relevant range spanning 38-41 degrees C in 0.01 M phosphate-buffered saline solution (pH = 7.4). We found that the poly(N-isopropylacrylamide-maleic acid) microgels showed an 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
226
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(237 citation statements)
references
References 22 publications
(29 reference statements)
5
226
0
4
Order By: Relevance
“…By incorporating gold nanorods into NIPAAm microgels, photo-induced heating of the gold nanorods provided enough heat to induce the phase transition of the microgel providing a possible photoinduced drug release [159]. With similar work on grafting NIPAAm onto gold nanoparticles being done by Pérez-Luna et al [160].…”
Section: Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating gold nanorods into NIPAAm microgels, photo-induced heating of the gold nanorods provided enough heat to induce the phase transition of the microgel providing a possible photoinduced drug release [159]. With similar work on grafting NIPAAm onto gold nanoparticles being done by Pérez-Luna et al [160].…”
Section: Particlesmentioning
confidence: 99%
“…Das et al showed another approach to polymer nanoparticle composites [159]. By incorporating gold nanorods into NIPAAm microgels, photo-induced heating of the gold nanorods provided enough heat to induce the phase transition of the microgel providing a possible photoinduced drug release [159].…”
Section: Particlesmentioning
confidence: 99%
“…The rate of reaction of the individual comonomers influences the final composition of the resulting polymer, according to the Mayo-Lewis equation [7]. The compositions used for the preparation of the polymers are extremely diverse; they include NIPA, the aforementioned initiators, comonomers like acrylic acid (AcA) [8], methacrylic acid and fumaric acid [9], acrylamide [10], maleic acid [11], hydroxyethyl methacrylate, N-vinylpyrrolidone [12] or N-tert-butyl acrylamide [13,14], as well as 4-pentenoic acid [15].…”
Section: Methodsmentioning
confidence: 99%
“…Nanocarriers typically target proteins, peptides, nucleic acids, DNA, and RNA [71,241,[248][249][250][251][252][253]. Polymeric structures and liposomes are usually employed as carriers, however, as stated above; polymers are large and cytotoxic and liposomes prone to leakage [254][255][256].…”
Section: Photothermal Transfectionmentioning
confidence: 99%